Effect of modified pre-milking sanitizing approaches on raw milk quality obtained from the dairy farmers of Tawau area, Sabah - Sim Kheng Yuen; Mohammad Raisul Alam (Turkish Science and Technology, 2016)
The aim of the study was to investigate the raw milk hygiene and quality among the small holder dairy farmers in Tawau area. A total of 216 samples were collected from the respective dairy farmers and milk collecting centre located at Mile 15, Tawau. Preliminary results indicated that the quality of the raw milks obtained at farm level contained were inferior with high bacteria load (> than 107 CFU/ml). The total coliform (2.9-3.8 CFU/mL) and Staphylococcus count (2.3-3.6 CFU/mL) were relatively high in certain samples. However, none of the food borne pathogens was found. Trace back study revealed that the causes of contamination were attributed by poor hygienic handling among the dairy farmers and insufficient for immediate chilling of raw milk. A significant reduction in bacteria load was observed if the raw milk chilled immediately at farm. The implementation of modified pre-milking sanitizing practices improved the microbiology quality of the raw milks obtained from respective dairy farms. Future study will focus more on the effect of prolong storage towards the microbiological quality of raw milk.